2022
DOI: 10.3390/cells11111775
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL12/CXCR4/ACKR3 Signaling Axis Regulates PKM2 and Glycolysis

Abstract: In response to CXCL12, CXCR4 and ACKR3 both recruit β-arrestin 2, regulating the assembly of interacting proteins that drive signaling and contribute to the functions of both receptors in cancer and multiple other diseases. A prior proteomics study revealed that β-arrestin 2 scaffolds pyruvate kinase M2 (PKM2), an enzyme implicated in shifting cells to glycolytic metabolism and poor prognosis in cancer. We hypothesized that CXCL12 signaling regulates PKM2 protein interactions, oligomerization, and glucose meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Specifically, the binding of CXCR4 to its ligand triggers the recruitment of β-arrestin molecules, which then initiates β-arrestin-dependent signaling through the activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2). Meanwhile, phosphorylated ERK1/2 drives pyruvate kinase M2 (PKM2) to upregulate glycolytic genes, triggering the pentose phosphate pathway and promoting glucose metabolism to a greater extent reshaping the metabolic reprogramming of cancer cells ( 49 ). Furthermore, by comparing the characteristics of 22 infiltrating immune cells in subgroups A and B, we found that the poor prognostic factors in subgroup A were closely associated with M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the binding of CXCR4 to its ligand triggers the recruitment of β-arrestin molecules, which then initiates β-arrestin-dependent signaling through the activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2). Meanwhile, phosphorylated ERK1/2 drives pyruvate kinase M2 (PKM2) to upregulate glycolytic genes, triggering the pentose phosphate pathway and promoting glucose metabolism to a greater extent reshaping the metabolic reprogramming of cancer cells ( 49 ). Furthermore, by comparing the characteristics of 22 infiltrating immune cells in subgroups A and B, we found that the poor prognostic factors in subgroup A were closely associated with M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…The following provides two examples. CXCL12 secreted by CAFs signals through receptors CXCR4 and/or ACKR3 to drive numerous processes required for tumor growth and metastasis, including proliferation, glycolytic metabolism, and migration/invasion [ 23 28 ]. CAFs secrete various isoforms of CXCL12 with CXCL12-γ, an isoform with high binding affinity to heparan sulfate proteoglycan extracellular matrix molecules, producing greatest effects to drive metastasis [ 29 ].…”
Section: Functions Of Cafsmentioning
confidence: 99%